Quality perception in a meat department of a retail store - Garza Quiroga, Juan Gilberto (Kansas State University, 2012)
HEB is a privately-held grocery retailer founded in 1905 in Kerrville, TX. Since then, HEB has grown to 399 stores in 155 communities. Although the majority of its operations have been in southern Texas, nearly 10 percent of HEB’s stores (39) are in Mexico. This may be considered an impressive feat since its entry into Mexico occurred in 1997 to take advantage of the growth opportunities in Mexico and the North American Free Trade Agreement involving Canada, the U.S. and Mexico. The research was conducted using primary data collected through a survey. Secondary data from the Shapiro Index were also employed to explain the observations from the survey. Econometric and statistical models were used in the analyses. Customer quality perception is an important metric for the retail industry. This research evaluates the effect of purchase history, frequency of shopping, price perception, quality and service changes through time on the quality perception of a meat department in a supermarket. The impact of additional labor was analyzed to determine the effect on those variables. The quality perception of the customers of other meat retailers in the same trading areas was also evaluated. The results of the study were then compared to the actual metric used to measure quality perception (Shapiro Index). The study found that the company has a significant higher quality perception than other supermarkets, that labor had a positive effect on quality and service change, customers noticed the change, and with time, it will increase their quality perception. The results show a different perception from customers than the Shapiro Index, customers do not notice a decrement on quality in the meat departments. Based on these results, a further research on the actual methodology used was performed, training and new purchasing specifications were applied to improve the intrinsic characteristics of the products and a new marketing campaign was launched based on quality and freshness.
Keywords: Consumer perception; Marketing; Quality; Economics, Commerce-Business (0505)